Potential Of A Void Diffusion Model To Predict Longwall Subsidence In The Illinois Coal Basin (International Conference on Ground Control in Mining, 1990)
In this paper, the authors attempt to apply a simplified non-homogeneous void diffusion model (NHVDM) to predict surface subsidence for longwall mining in Illinois. A generalized error function subsidence profile is derived from this model. The model validation indicates that the NHVDM approach appears to fit the observed subsidence data as well or better than the error and the trigonometric functions, particularly around the trough edge areas.